Design of a multistage anti-jam GPS receiver - DI Min-min; ZHANG Er-yang (Tongxin xuebao)
Since the anti-jam capability of joint space-time processing used in GPS depended on the number of antenna elements, a multistage anti-jam GPS receiver was proposed. It was of low complexity compared to the joint space-time processing receiver with the same anti-jam capability. Finally the simulation results presented prove it is of advantage in decreasing computation complexity and improve anti-jam capability.